(untitled) (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study aims to understand the process of internalizing character values based on Sundanese local wisdom, known as Pancawaluya: cageur, bageur, bener, pinter, and singer in karate. This research uses a qualitative method with a case study design. The data analysis technique used in this study is the interactive model by Miles & Huberman, which includes: data reduction, data display, and conclusion drawing/verification. The sampling technique used in this study is purposive sampling. The data collection techniques used in this research include interviews, observations, and documentation. The results show that the value of cageur is implemented through instilling discipline in physical training, hard work, and a healthy lifestyle. The value of bageur is manifested through habituating social care, humility, environmental awareness, and preserving local culture. The value of bener is reflected in religious habituation, honesty, courage, justice, sportsmanship, and love of the homeland. The value of pinter is implemented by developing an intelligent, wise, and creative character. The value of the singer is implemented by fostering integrity, responsiveness, agility, and responsibility in students. The internalization of character values based on local wisdom in karate practice can strengthen the moral, social, spiritual, and national dimensions of karate practitioners. Thus, karate is not only positioned as a sport for achievement but also as a character education vehicle that aligns with the cultural values of the nation.